Experimental investigation on the heat dissipation performance of flared-fin heat sinks for concentration photovoltaic modules. (5th July 2019) - Luo, Qi; Li, Penghui; Cai, Lanlan; Chen, Xindong; Yan, Han; Zhu, HanXing; Zhai, Pengcheng; Li, Peng; Zhang, Qingjie
Highlights: A flared fin heat sink is proposed to meet high-density heat dissipation of CPV. Natural convection of flared fin heat sink was tested under different conditions. Thermal resistance of flared fin was reduced 10% compared to rectangular fin. A Nusselt number correlation is presented for the design of flared fin heat sink. Abstract: A high-efficiency, low-cost and convenient cooling method plays a critical role in the thermal management of the solar cell temperature of the concentrating photovoltaic system (CPV). In this research, an improved flared-fin heat sink was proposed to meet the high-density heat dissipation requirement of CPV. The overall thermal resistance of 15 heat sink samples with different fin number and fin length is experimentally investigated under various inclination angles. The results demonstrate that the overall thermal resistance of the flared-fin heat sink is decreased by 10% but not significantly increased in the weight and volume while comparing with a rectangular plate-fin heat sink. The thermal performance is greatly impacted by the fin number and fin length of the flared-fin heat sink but is not very sensitive to the inclination angle. The optimal fin numbers for maximum heat transfer was found to be 15–18 under the experimental conditions and has nothing to do with the inclination angle. Moreover, the Nusselt number correlation of the proposed flared-fin heat sink is presented for facilitating the design of CPV systems when the Rayleigh number Ras, number of fins Nfin, and fin length Lfin are in the ranges 10 2 < R a S < 10 6, 3 < N fin < 19 and 35 < L fin < 115 m m, respectively.